2021
DOI: 10.3390/pharmaceutics13060799
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Loading of Idarubicin in CalliSpheres® Drug-Eluting Beads and Characterization of Release Profiles and Morphological Properties

Abstract: This study aimed to investigate the idarubicin loading method, compatible stability with contrast agent, release profiles, and morphological properties of 50–150, 100–300, and 300–500 μm CalliSpheres®. The amounts of idarubicin added, loading medium, loading condition, and drug concentration were investigated as factors influencing drug loading efficiency. The drug loading rate was negatively correlated with the amount drug added and diameter of CalliSpheres® and positively correlated with the drug concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Notably, CB is reported as an ideal drug carrier of apatinib, idarubicin, arsenic trioxide, etc. [ 10 , 41 , 42 ]. Combined with previous literatures, we concluded that the lidocaine/CalliSpheres ® composites were successfully prepared, and exhibited preliminary application potential as drug carriers.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, CB is reported as an ideal drug carrier of apatinib, idarubicin, arsenic trioxide, etc. [ 10 , 41 , 42 ]. Combined with previous literatures, we concluded that the lidocaine/CalliSpheres ® composites were successfully prepared, and exhibited preliminary application potential as drug carriers.…”
Section: Resultsmentioning
confidence: 99%
“…CalliSpheres DLMS is a new type of drug-loaded microsphere system, and its volume will be signifcantly reduced after drug loading. After 20 days of interventional therapy, with the gradual release of chemotherapy drugs, the volume of CalliSpheres DLMS will gradually recover, so it can efectively block the blood vessels supplying tumors and prolong the recanalization time of the blood vessels supplying tumors [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…It carries an anionic sulfonic acid group and cationic amino group of chemotherapy drugs for exchange to complete drug loading. Studies have shown that DEB can accelerate the loading of drugs in a 5% glucose solution [ 40 42 ]. DEB can be divided into five types according to the diameter: 100 ~ 300, 300 ~ 500, 500 ~ 700, 700 ~ 900, and 900 ~ 1200 μm.…”
Section: Callisperes ® Of Drug-loaded Microspherementioning
confidence: 99%